ANALISIS TINGKAT KEPUASAN PELANGGAN ATAS KUALITAS LAYANAN DAN HARGA PADA INDOMARET KECAMATAN BANDAR SEIKIJANNG KABUPATEN PELALAWAN - Putri, Hutagalung; Aida Nursanti, Aida Nursanti; Jushermi, Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The aim of this research is to determine the level of customer satisfaction at Indomaret, Bandar Seikijang District, Pelalawan Regency in terms of service quality based on the physical evidence dimension (tangible), reliability (reliability), responsiveness (responsiveness), guarantee (assurance), empathy (empathy), and prices, regarding the quality of service and prices at Indomaret, Bandar Seikijang sub-district, Pelalawan Regency. The population in this study were all unknown customers of Indomaret, Bandar Seikijang District, Pelalawan Regency (indefinite), with a sample size of 100 respondents. Primary data was collected using a questionnaire as an instrument to prove the research results, to test the hypothesis in this research using the method Importance Analysis Performance (IPA) with the program Statistical Product and Service (SPSS) version 25. The results of this research show that the comparison results between performance and negative expectations (less satisfied) were obtained. This negative gap shows that the performance of Indomaret, Bandar Seikijang District, Pelalawan Regency is still below customer expectations. With the biggest gap lying in dimensions tangible on employee appearance attributes and the lowest gap lies in the price variable on the attribute of price suitability with product quality as much as possible. Meanwhile, in the Cartesian diagram, quadrant I is the main priority quadrant where there are 9 items that must be repaired immediately. Keywords: Customer Satisfaction, Service Quality, Price,, Importance Analysis Performance (IPA)